Constitutional analysis: Right to the life of the unborn child, in the face of the decriminalization of abortion - Díaz Peña, Isabel Andrea (2025)
The unborn child develops in a condition of vulnerability, because its development depends on the process of the mother's womb and it is in this way that the protection of the woman's righs in relation to those who are unborn is born. The objective is to analyze the constitutional framework of protection and application of the right to the life of unborn children in Ecuador, related to the decriminalization of abortion due to rape. The approach is qualitative, descriptive, with documentary design. A review of Ecuadorian jurisprudence and academic databases such as Dialnet, Redalyc and Scielo was carried out. The results reveal that the decriminalization of abortion for rape poses challenges, which strains the protection of the right to life since conception with reproductive rights and women's health. It is concluded that the legalization of abortion would imply a transgression of the right to life, and would undermine the essential principles of human dignity and the protection of the most defenseless